FREQUENCY OF REVEALING CHLAMYDIA IN THE THROAT IN SCHOOLCHILDREN BY MEANS OF DIRECT IMMUNOFLUORESCENCE - T. A. Kapustina; E. V. Belova; T. A. Kin (LLC "Diagnostics and Vaccines", 2015)
The article presents information on the prevalence of chlamydial infection of the upper respiratory tract in schoolchildren. Researchers have shown specific structure of the identified chlamydia depending on gender and age of the patients, as well as the prevalence of children with positive chlamydial antigens of acute and of chronic upper respiratory disease, compared with uninfected children. These results are based on a survey of 708 schoolchildren between the ages of 7 and 14 years. Chlamydia diagnosis was performed by direct immunofluorescence.